2013
DOI: 10.1128/jvi.02675-12
|View full text |Cite
|
Sign up to set email alerts
|

Differential Targeting of Viral Components by CD4+versus CD8+T Lymphocytes in Dengue Virus Infection

Abstract: Dengue virus (DENV) is the principal arthropod-borne viral pathogen afflicting human populations. While repertoires of antibodies to DENV have been linked to protection or enhanced infection, the role of T lymphocytes in these processes remains poorly defined. This study provides a comprehensive overview of CD4(+) and CD8(+) T cell epitope reactivities against the DENV 2 proteome in adult patients experiencing secondary DENV infection. Dengue virus-specific T cell responses directed against an overlapping 15me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
193
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(209 citation statements)
references
References 48 publications
14
193
0
2
Order By: Relevance
“…T cell lines were incubated overnight at 37°C with pools of HBV peptides (5 μg/ml), where final DMSO concentrations did not exceed 0.5%. IFN-γ ELISPOT assays (Millipore) were performed as described previously (28).…”
Section: Discussionmentioning
confidence: 99%
“…T cell lines were incubated overnight at 37°C with pools of HBV peptides (5 μg/ml), where final DMSO concentrations did not exceed 0.5%. IFN-γ ELISPOT assays (Millipore) were performed as described previously (28).…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that maternal antibodies inhibit seroconversion upon PDK53 vaccination in pups born to PDK53-immune dams. However, we hypothesized that vaccination of these pups with PDK53 may still induce T cell-mediated protection, which usually targets the more conserved nonstructural proteins (17,18,38,39). It was indeed reported that the T cell response to vaccination was not impaired by maternal antibodies (29).…”
Section: Pdk53 Vaccination Protected Against D2y98p-pp1 In the Contexmentioning
confidence: 97%
“…Además, se ha demostrado que la proteína NS3 es una proteína inmunodominante y uno de los blancos más significativos de la reacción de los linfocitos T durante la infección con el DENV (7,8). Todas estas características la han convertido en un blanco terapéutico valioso y, por lo tanto, en un objeto interesante de estudio.…”
unclassified